2016
DOI: 10.1155/2016/8098657
|View full text |Cite
|
Sign up to set email alerts
|

A Scaphoid Stress Fracture in a Female Collegiate-Level Shot-Putter and Review of the Literature

Abstract: Scaphoid stress fractures are rare injuries that have been described in young, high-level athletes who exhibit repetitive loading with the wrist in extension. We present a case of an occult scaphoid stress fracture in a 22-year-old female Division I collegiate shot-putter. She was successfully treated with immobilization in a thumb spica splint for 6 weeks. Loaded wrist extension activities can predispose certain high-level athletes to sustain scaphoid stress fractures, and a high index of suspicion in this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Stress fractures of the scaphoid caused by repetitive microtrauma are uncommon, and only a few case reports exist in the literature. 5 Patients often report only nonspecific wrist pain, and correct diagnosis is often delayed. Therefore, assessing with reasonable certainty whether the increasing pain 1 year after the first procedure in our patient was caused by the concomitant scaphoid stress fracture dating back some time, the lunocapitate joint OA alone, or a combination of both was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Stress fractures of the scaphoid caused by repetitive microtrauma are uncommon, and only a few case reports exist in the literature. 5 Patients often report only nonspecific wrist pain, and correct diagnosis is often delayed. Therefore, assessing with reasonable certainty whether the increasing pain 1 year after the first procedure in our patient was caused by the concomitant scaphoid stress fracture dating back some time, the lunocapitate joint OA alone, or a combination of both was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…5 Kohring et al recently reviewed the literature regarding scaphoid stress fracture and identified 16 cases (12 unilateral, 4 bilateral). 6 Nine of the cases were treated nonoperatively and seven with internal fixation (two after nonunion following initial nonoperative treatment). All fractures were reported to have united and the patients returned to highlevel sport with no further problems.…”
Section: Discussionmentioning
confidence: 99%
“…Other signs of scaphoid fracture are pain with longitudinal thumb compression (sensitivity 100%, specificity 48%), and on palpating the scaphoid tubercle (sensitivity 100%, specificity 30%). It is a good practice to compare both wrists during the examination [10][11][12]. Decrease of the grip strength by more than 50% as compared to the contralateral side increases the positive predictive value for a scaphoid fracture [13,14].…”
Section: Discussionmentioning
confidence: 99%